Antibodies against HPV16E6 oncoprotein in the Swiss HIV cohort study: Kinetics and anal cancer risk prediction. Issue 3 (4th December 2019) - Combes, Jean‐Damien; Clifford, Gary M.; Günthard, Huldrych F.; Hauser, Christoph; Darling, Katharine E.A.; Valladares, Pablo; Battegay, Manuel; Waldeck, Frederike; Bernasconi, Enos; Bertisch, Barbara; Hirsch, Hans H.; Brenner, Nicole; et al.
Abstract : Our aim was to describe HPV16E6 antibody kinetics prior to anal cancer in people living with HIV/AIDS (PLWHA) and evaluate the possible contribution of HPV16E6 serology to anal cancer risk prediction. For 91 persons diagnosed with anal cancer in the Swiss HIV Cohort Study (1989–2017), serial serum/plasma samples were tested for HPV16E6 antibodies using multiplex serology, supplemented with samples from 1, 356 participants without anal cancer. Anal cancer incidence was estimated for PLWHA from 40 years‐old in the cART era, stratified by HPV16E6 serostatus. HPV16E6 seroprevalence was 23.3% in samples <2 years prior to anal cancer diagnosis and decreased with increasing time prior to cancer: 16.7% at 2–4 years, 4.4% at 5–9, and 7.0% at ≥10 years. Of 25 individuals with anal cancer who were HPV16E6‐seropositive at any time during follow‐up, the majority ( n = 18) remained seropositive in all samples after seroconversion, whereas for seven cases, seropositivity was transitory. Among individuals with anal cancer, HPV16E6 seroprevalence was marginally higher in women vs . men who have sex with men (adjusted OR = 4.3, 95% CI: 1.1, 17.2) and in older participants (adjusted OR = 6.2, 95% CI: 1.1, 34.8 for cases diagnosed at ≥55 vs . <45 years). Anal cancer incidence was 402/100, 000 person‐years in HPV16E6‐positive vs . 82/100, 000 in HPV16E6‐negative PLWHA (incidence rate ratio = 4.9, 95% CI: 1.3, 13.1). In conclusion, HPV16E6 serology, despite its low sensitivity, allows characterization of a group of individuals with very high anal cancer incidence and may have a place in secondary prevention in groups at high risk for anal cancer such as PLWHA. What's new?: Infection with human immunodeficiency virus (HIV) significantly increases anal cancer risk. Anal cancer is further associated with the presence of antibodies against human papillomavirus type 16 protein E6 (HPV16E6), indicative of HPV16 infection. In this study, using serial samples from the Swiss HIV cohort study (1989–2017), the authors analyzed HPV16E6 seroprevalence prior to anal cancer diagnosis. In HIV‐infected persons, HPV16E6 antibodies were detected in just under one‐quarter of samples less than two years before anal cancer detection. The findings suggest that, despite low sensitivity, HPV16E6 serology could be a useful means of predicting anal cancer risk.